STUDY OF OVERPRESSURE CHARACTERISTIC IN ANOA FIELD, WEST NATUNA BASIN, RIAU ISLANDS - Isnania Putri, Nurul
The Anoa Field is located in the West Natuna Basin, in the western part of the Natuna Sea, operated by Premier Oil Natuna Sea B.V. The stratigraphy of the Anoa Field is divided into six formations, i.e. Lama, Benua, Lower Gabus, Keras, Upper Gabus, and Muda formations. The study is performed in these six formations, which are Late Eocene – Recent in age. The purpose of this study is to estimate pore pressure, determine the top of overpressure, determine the overpressure generating mechanism, and analyse the relationship between overpressure and geological condition in the study area. The study is performed in 2 drilling wells by using wireline log data, seismic interval velocity data, pressure test data, temperature data, well report, and geological data. The result of data analysis shows that both wells have overpressure condition. The top of overpressure varies from 7400 – 7600 ft TVDSS, with the magnitude of pore pressure is around 3200 – 5800 psi or 8.2 – 10.4 ppg. The top of overpressure relatively follows the top of the Benua Formation. The main overpressure generating mechanism in the Anoa Field is loading mechanism, which is caused by the deposition of the Muda Formation. The minor mechanism which is thought to be contributed to the overpressure generating mechanism in the study area is clay mineral diagenesis.